Long colonnade on the ground floor of the Matha - Temples of India Project Team (Jio Institute, 2024)
The ground floor of the matha (monastic or residential building) of the Suhaveshwar Temple has a long colonnade on its front side. There are four pillars to the colonnade flanking the main entrance. These pillars are equidistant to one another. At the end of the colonnade, there is a small cell.